Integral fault analysis of the ARIA cipher - Yu SHEN; Wei LI; Dawu GU; Yixin WU; Shan CAO; Ya LIU; Zhiqiang LIU; Zhihong ZHOU (Tongxin xuebao)
ARIA is a Korean standard block cipher,which is flexible to provide security for software and hardware implementation.Since its introduction,some research of fault analysis is devoted to attacking the last two rounds of ARIA.It is an open problem to know whether provoking faults at some former rounds of ARIA allowed recovering the secret key.An answer was given to solve this problem by showing a novel integral differential fault analysis on two rounds earlier of ARIA.The mathematical analysis and simulating experiments show that the attack can successfully recover its secret key by fault injections.The results in this study describe that the integral fault analysis is a strong threaten to the security of ARIA.The results are beneficial to the analysis of the same type of other block ciphers.